2006
DOI: 10.1159/000093450
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin or Anticoagulants in Stenosis of the Middle Cerebral Artery:A Randomized Trial

Abstract: Background: We report the results of an open, randomized, multicenter trial that compared the efficacy of aspirin to oral anticoagulants (OA) for the prevention of vascular events in patients with symptomatic stenosis of the middle cerebral artery (MCA). Methods: Participants were randomly assigned to receive 300 mg/day of aspirin or a dose of OA (target INR 2–3). The MCA stenosis was demonstrated by conventional angiography or by at least two noninvasive examinations. Patients had either transient ischemic at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 66 publications
0
12
0
1
Order By: Relevance
“…385,[565][566][567][568][569][570] Most of these trials enrolled patients with heterogeneous causes of stroke such as large-artery extracranial or intracranial atherosclerosis, small-vessel disease, or cryptogenic stroke, but 2 of these studies 385,568 restricted enrollment to patients presenting with TIA or stroke related to atherosclerotic intracranial arterial stenosis. None of these randomized trials have shown a benefit of VKAs over antiplatelet therapy for preventing recurrent stroke, whereas some of these trials have shown an increased risk of major hemorrhage in the VKA arm.…”
Section: Oral Anticoagulantsmentioning
confidence: 99%
“…385,[565][566][567][568][569][570] Most of these trials enrolled patients with heterogeneous causes of stroke such as large-artery extracranial or intracranial atherosclerosis, small-vessel disease, or cryptogenic stroke, but 2 of these studies 385,568 restricted enrollment to patients presenting with TIA or stroke related to atherosclerotic intracranial arterial stenosis. None of these randomized trials have shown a benefit of VKAs over antiplatelet therapy for preventing recurrent stroke, whereas some of these trials have shown an increased risk of major hemorrhage in the VKA arm.…”
Section: Oral Anticoagulantsmentioning
confidence: 99%
“…Aspirin has been shown to reduce the risk of stroke [1] and is the treatment of choice for the prevention of vascular events in patients with symptomatic middle cerebral artery (MCA) stenosis [2]. Standard extracranial-intracranial (EC-IC) arterial bypass surgery is a treatment option to revert hemodynamic compromise in order to avoid recurrent ischemic stroke in patients with symptomatic, chronic, hemodynamic insufficiency [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Among trials the different event rates may be attributed to study design features, the vascular risk profile of the included patients and the intensity of cointerventions for other vascular risk factors or comorbidity. Restricting access to the randomized trial to patients with high-risk conditions like atrial fibrillation or large-artery atherosclerosis will increase the number of endpoints [3,4,5,6]. Including only patients with multiple risk factors or previous vascular events may also increase the endpoint rate.…”
Section: Introductionmentioning
confidence: 99%